The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1161/01.res.45.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Some bases of differences in vascular response to sympathetic activity.

Abstract: IN 1858 Claude Bemarde summarized much of his research into the physiology of the control of the circulation by the statement that the sympathetic nervous system acted as a "vasoconstrictor nerve." Subsequent study has shown that this division of the autonomic nervous system, although not always constrictor, exerts a control over the tone of both arteries and veins, which is of profound physiological significance. The influence on a particular vascular segment, however, varies widely, both qualitatively and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 93 publications
3
43
0
1
Order By: Relevance
“…In small muscular arteries and arterioles, the distance between sympathetic nerve endings and smooth muscle cells is short, and responses to NE are fast and initially great but not maintained over time. In larger arteries, the distance between synapses and smooth muscle cells is greater, and since NE relies both on diffusion and neuronal reuptake within the vessel wall, this results in a slower and smaller response but is maintained over time (3). It may be hypothesized that women primarily rely to a larger extent on arterial vasoconstriction of smaller arteries, i.e., fast but not maintained, whereas men rely on vasoconstriction in larger arteries with slower but maintained responses over time (3,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In small muscular arteries and arterioles, the distance between sympathetic nerve endings and smooth muscle cells is short, and responses to NE are fast and initially great but not maintained over time. In larger arteries, the distance between synapses and smooth muscle cells is greater, and since NE relies both on diffusion and neuronal reuptake within the vessel wall, this results in a slower and smaller response but is maintained over time (3). It may be hypothesized that women primarily rely to a larger extent on arterial vasoconstriction of smaller arteries, i.e., fast but not maintained, whereas men rely on vasoconstriction in larger arteries with slower but maintained responses over time (3,31).…”
Section: Discussionmentioning
confidence: 99%
“…In larger arteries, the distance between synapses and smooth muscle cells is greater, and since NE relies both on diffusion and neuronal reuptake within the vessel wall, this results in a slower and smaller response but is maintained over time (3). It may be hypothesized that women primarily rely to a larger extent on arterial vasoconstriction of smaller arteries, i.e., fast but not maintained, whereas men rely on vasoconstriction in larger arteries with slower but maintained responses over time (3,31). The more pronounced return in FBF during LBNP and the initially faster but less maintained arm capacitance response as well as decreased net capillary fluid absorption in women support this theory (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Since ergot alkaloids, such as ergotamine and ergonovine, have complex pharmacological properties with potential actions at dopaminergic and serotonergic as well as a-adrenergic receptors (MiillerSchweinitzer and Weidmann, 1978), and arteries from different vascular beds are pharmacologically heterogeneous (Bevan, 1979), it is important to clarify the nature of the contractile response to ergonovine of arteries from different vascular beds. Irr recent studies, we have demonstrated that atherosclerotic aortas from rabbits fed a high-cholesterol diet are supersensitive to the constrictor effects of ergonovine (Henry and Yokoyama, 1980).…”
mentioning
confidence: 99%
“…The action mechanisms are not well established [6,10,11] and not clearly understandable theoretically. The smooth muscles (SM) of large and medium-sized veins studied in vitro had no tone and did not relax under the impact of vasodilators [12]. The lumen of collapsed veins is slit-like, the circular SM layer is thin, bunches of SM alternating with connective tissue.…”
Section: Sirmentioning
confidence: 99%